Experimental study on pp-band mesh seismic retrofitting For low earthquake resistant arch shaped roof masonry houses - Sathiparan, N.; Mayorca, P.; Meguro, K. (My University, 2009)
Unreinforced masonry structure is one of the most popularly used constructions. It is also unfortunately the most vulnerable to the earthquakes. It would collapse within a few seconds during earthquake movement, and does become a major cause of human fatalities. Therefore, retrofitting of low earthquake-resistant masonry structures is the key issue for earthquake disaster mitigation to reduce the casualties significantly. When we propose the retrofitting in developing countries, retrofitting method should respond to the structural demand on strength and deformability as well as to availability of material with low cost including manufacturing and delivery, practicability of construction method and durability in each region. Considering these issues, a technically feasible and economically affordable PP-band (polypropylene bands, which is commonly utilized for packing) retrofitting technique has been developed and many different aspects have been studied by Meguro Laboratory, Institute of Industrial Science, The University of Tokyo. Unreinforced masonry structures with masonry arch shaped roofs are generally characterized by weak, brittle materials, weak element connections and excessive weight. The main points of weakness of the traditional masonry arch roofs that contributed to poor seismic response can be inability of the roof to act as a diaphragm and heavy weight of the roof. But ability of PP-band mesh kept the structure integral during the shaking will help to overcome this issues. Therefore, to evaluate the beneficial effects of the PP-band mesh retrofitting method, shaking table tests were carried out on arch shaped roof masonry structure with and without retrofitting. From tests’ results, a scaled model with PP-band mesh retrofitting is able to withstand larger and more repeatable shaking than that without PP band retrofitting, which all verified to reconfirm high earthquake resistant performance. Therefore proposed method can be one of the optimum solutions for promoting safer building construction in developing countries and can contribute earthquake disaster reduction in future.